POTATO SEED PRODUCTION IN RUSSIA - Anisimov, Boris (Potato Journal, 2019)
Potato J (2018) 45 (2): 152-158 POTATO SEED PRODUCTION IN RUSSIA B Anisimov1, E Simakov1, A Mityushkin1, A Zhuravlev1, E Blinkov1 and K Arshin1 ABSTRACT: Detailed knowledge of the actual problems of production of seed potatoes is extremely important for theÂ development of the Russian andÂ nternational potato market in general. The authors propose special phytosanitary requirements to the virus and bacterial diseases of potato that are to be obeyed within the selected potato seed productionÂ zones. A special attention is devoted to the cultural practices helping to reduce exposure of infections and minimize their spread via control of vectors. This paper presents the information regarding seed potato quality improvement in Russia.